Comparison of various advanced oxidation processes used in remediation of industrial wastewater laden with recalcitrant pollutants - Krishnan, S. (Institute of Physics Publishing, 2017)
Due to the scarcity of water, it has become a necessity to improve the quality of wastewater that is discharged into the environment. Conventional wastewater treatment can be either a physical, chemical, and/or biological processes, or in some cases a combination of these operations. The main purpose of wastewater treatment is to eliminate nutrients, solids, and organic compounds from effluents. Current wastewater treatment technologies are deemed ineffective in the complete removal of pollutants, particularly organic matter. In many cases, these organic compounds are resistant to conventional treatment methods, thus creating the necessity for tertiary treatment. Advanced oxidation process (AOP), constitutes as a promising treatment technology for the management of wastewater. AOPs are characterised by a common chemical feature, where they utilize the highly reactive hydroxyl radicals for achieving complete mineralization of the organic pollutants into carbon dioxide and water. This paper delineates advanced oxidation processes currently used for the remediation of water and wastewater. It also provides the cost estimation of installing and running an AOP system. The costs are separated into three categories: capital, operational, and operating & maintenance. © Published under licence by IOP Publishing Ltd.